On robust state estimation for power system with uncertain network parameters - Uatrongjit,S. (2015)
© 2014 IEEE. This paper presents a robust state estimation method for a power system which its transmission line network parameters are only known to lie within some bounds. Voltage magnitude, power injection and power flow collected by remote terminal units are used as measurement quantities and the state variables are bus voltage phasor expressed in rectangular coordinates. Hence, the relation between measured data and state variables becomes quadratic function. The problem of state estimation with uncertain but bounded network parameters is formulated as a robust optimization. A solution method based on finding fixed-point of the map obtained by solving a semi-definite programming is also presented. Some preliminary testing results on the IEEE 14-bus are given.